Review of Pitcher Plants of the Old World - Christenhusz, Maarten J.m.; Fay, Michael F. (Phytotaxa, 2009)
Carnivorous plants have fascinated humans since early history, and these plants continue to tickle the imagination of current day writers. Stewart McPherson shares his fascination for carnivorous plants and he has published various earlier works on the subject, including the excellent Pitcher Plants of the Americas(McPherson, 2006) and Glistening Carnivores (McPherson, 2008), where, as in the current two volumes, many carnivorous plants are described and beautifully illustrated with photographs taken by the author during his intensive field work in often challenging countries and stunning localities.